Narratives of (Mad) Desire - Airaksinen, Timo (ETHICS IN PROGRESS, 2013)
Satisfied desires make you happy. Desires are fantasy narratives a  person tells about her life and goals. They focus on intentional objects that are happiness-makers for the person: to achieve them is supposed to make one happy. Normally, such objects are good things and their context is seen in a positive manner. However, the goals may also be hurtful, as the person herself sees it. These are, at least sometimes, mad desires. To explain them, it is not enough to say that they are impulsive and irrational, unconscious, or that they are good in disguise. I explain what this means and give some examples. I also consider the thesis that satisfaction of desire is less than full happiness, which may well be true. This becomes clear when we think of moral choices.